Synchronized Offset Stacking: A Concept for Growing Large-Domain and Highly Crystalline 2D Covalent Organic Frameworks - Auras, Florian; Ascherl, Laura; Haldmioun, Amir H.; Margraf, Johannes; Hanusch, Fabian C.; Reuter, Stephan; Bessinger, Derya; Doeblinger, Markus; Hettstedt, Christina; Karaghiosoff, Konstantin; Herbert, Simon; Knochel, Paul; et al. (Journal of the American Chemical Society, 2016)
Covalent organic frameworks (COFs), formed by reversible condensation of rigid organic building blocks, are crystalline and porous materials of great potential for catalysis and organic electronics. Particularly with a view of organic electronics, achieving a maximum degree of crystallinity and large domain sizes while allowing for a tightly pi-stacked topology would be highly desirable. We present a design concept that uses the 3D geometry of the building blocks to generate a lattice of uniquely defined docking sites for the attachment of consecutive layers, thus allowing us to achieve a greatly improved degree of order within a given average number of attachment and detachment cycles during COF growth. Synchronization of the molecular geometry across several hundred nanometers promotes the growth of highly crystalline frameworks with unprecedented Spectroscopic data indicate considerable delocalization of excitations along the pi-stacked columns and the feasibility of donor-acceptor excitations across the imine bonds. The frameworks developed in this study can serve as a blueprint for the design of a broad range of tailor-made 2D COFs with extended pi-conjugated building blocks for applications in photocatalysis and optoelectronics.